How the timing and location of video shows influence learning among rice farmers in Uganda - Karubanga, Gabriel; Kibwika, Paul; Okry, Florent; Sseguya, Haroon (International Journal of Agricultural Research, Innovation and Technology, 2017)
Videos have the potential of enhancing learning among smallholder farmers. The study intended to establish whether timing and location of video shows influence learning among rice farmers in Kamwenge district, Uganda. A cross-sectional study was conducted by interviewing 48 focus group participants; 100 individual video participants and 16 key informants. Geographical Positioning System (GPS) mapping was used to establish the video catchment areas and distribution of video participants. Farmers approved the video for providing timely, useful and reliable information and bringing extension service providers closer to the farming communities. Majority (94%) of the farmers said that video provided useful information that fostered change in rice production practices and technologies. A one sample T-test indicated that the timing and location of video events are significant in influencing learning among farmers particularly by women, elderly and distant farmers. The implication is that locating video shows far away and running them late at night seriously compromised involvement by females, elderly and distant people. Thus, modalities suggested by farmers need to focus on adjusting the timing of video shows and ensuring rotational operational of videos in the respective villages or parishes purposely to reach out to the elderly, distant and women farmers. Int. J. Agril. Res. Innov. & Tech. 6 (2): 77-81, December, 2016